Dynamics and territorial management of Constantine: Challenges and perspectives - SEGUIA, Saoussene; CHERRAD, Salah Eddine (Journal of Human Sciences, 2020)
The territorial management is a concept of bringing actors together, and adapting to territorial developments which requires a collective dimension. In connection with Constantine, its out-of-town extension without being followed by institutional reforms, its saturated historic center and an ignored actor’s logic are considerations that challenge this concept. So this observation presupposes the actions undertaken according to two factors, the first exogenous related to national decisions and the second endogenous goes back hundreds of years. The main objective of this study is to analyze the dynamics of Constantine territory. To do this, an assessment was carried out on the development of Constantine territory in the neighboring municipalities and in parallel a de-densification of the mother city. The limit of regulatory urban planning instruments and the historical specificity of Constantine call for territorial management to combine distinct territories and articulate different dynamic elements. La limite des instruments d’urbanisme réglementaire et la spécificité historique de Constantine appellent à un management territorial qui combine des territoires distincts et articule différents éléments dynamiques.